Posibilidades y manejo del fracaso terapéutico de la hidronefrosis congénita. - Delgado Martín, J.A.; Jiménez Penick, F.J.; Moreno Sierra, Jesús; Silmi Moyano, A. (Clínicas Urológicas de la Complutense, 2002)
Sin resumen